Ultrasound investigation central hemodynamics as a method of assessment effective analgesia in children - K. Y. Dmytriieva (Kazimierz Wielki University, 2016)
Dmytriieva K. Y. Ultrasound investigation central hemodynamics as a method of assessment effective analgesia in children. Journal of Education, Health and Sport. 2016;6(6):207-212. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55301 http://ojs.ukw.edu.pl/index.php/johs/article/view/3571   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   ULTRASOUND INVESTIGATION CENTRAL HEMODYNAMICS AS A METHOD OF ASSESSMENT EFFECTIVE ANALGESIA IN CHILDREN   K. Y. Dmytriieva   Vinnitsa National Medical University M.I. Pirogov   Summary: The study was include in 23 children (12,4±1,2 years) operated on for tumors of the retroperitoneal space (14 children, 61%), renal tumors (6 children, 26%), ovarian cancer (3 children, 13%) showed that a comprehensive study of the reactions of pain behavior and central hemodynamics by ultrasonography showed that the use of the scheme KSME bupivacaine 0.3-0.4 mg / kg and a continuous infusion of drugs (fentanyl in a dose of 10 mcg/kg/h) for postoperative pain relief leads to effective analgesia after traumatic operations and comprehensive ultrasound including color and spectral Doppler studies, is the main tool by enabling timely and accurately assess the condition of the central hemodynamics at different methods of analgesia.   Key words: central hemodynamics, ultrasound, anesthesia.